Errors in Latin Inscriptions on Renaissance Works of Fine Art - Lazer-Pankiv Olesia; Korolova Nataliia (Darnioji daugiakalbystė)
Ever wider spread of the Latin language in Europe during the Renaissance period resulted in de facto bilingual society. Latin grew into a cultural code to understanding the ancient high culture heritage though in everyday life people kept using local dialects. Classical Latin was also used as the language of education and by the 15th century, most of the aristocratic elites had achieved a high-level proficiency in Latin. The desire to become a part of the elite class pushed artists, their customers, friends or relatives to place Latin inscriptions on works of fine art. Occasionally they even hired experts to create the text for the inscriptions. However, they were not always well-educated humanists and connoisseurs of the classical Latin, therefore the inscriptions contain numerous errors both in the original, custom-made texts and in quotations from ancient works. The analysis of the Latin inscriptions on paintings, frescoes and engravings of the Renaissance period shows that the most common errors are phonetic and orthographic. This reflects the peculiarities of the pronunciation of Latin letters and letter combinations in this period: use of digraphs (ae, ое), alternation of letters е-а, oe, o-u, а-о, replacement of y with i, simplification in writing doubled consonants, interchange of ti and ci, parallel use of letters k and c, substitution of Greek aspirates with single-grapheme counterparts etc. Fewer are the errors of the morphological (declension) and syntactic (use of syntactic constructions, agreement, etc.) levels. Even rarer are the lexical deviations from the norms of classical Latin: most of the vocabulary of the inscriptions comes from the classical period. The desire to avoid incorrect use of certain forms often led to hypercorrection. In some cases, the errors were made because the artists did not understand the meaning of the inscription.